GAMBARAN HASIL PEMERIKSAAN KADAR KOLESTEROL PADA PENDERITA HIPERTENSI DI RSUD SYEKH YUSUF KABUPATEN GOWA - Muh Rizman Naim; Sri Sulastri; Sulvana Hadi (Jurnal Media Laboran, 2019)
Cholesterol is a component of fat or lipid substances as we know, fat is one of the nutrients that are needed by our body in addition to other nutrients, such as carbohydrates, proteins, vitamins and minerals. Fat is one of the energy sources that provides the highest calories. Apart from being a source of energy, fat or especially cholesterol is indeed the substance most needed by our body and has an important role in human life. This study aims to determine the description of the results of cholesterol levels in patients with hypertension at Syekh Yusuf Hospital Gowa Regency. The research carried out was a quasi-experimental study that carried out laboratory tests to determine the description of the results of cholesterol levels in patients with hypertension at Syekh Yusuf Regional Hospital, Gowa Regency. The sample in this study was hypertension sufferers in Syekh Yusuf Regional Hospital, Gowa Regency. The results showed that the results found in the analysis of variable cholesterol levels in the sample were not balanced, as many as 1 person (5%) had high cholesterol levels and 19 people (95%) had normal cholesterol levels. Based on the results of the study it can be concluded that the cholesterol level in RSUD Syekh Yusuf Gowa Regency there is a balanced increase so that it can be concluded that the patient's cholesterol level is at normal limits.